Molecular Characterization of a Novel Mucopolysaccharidosis (MPS) type VI-causing Mutation – Indirect Proof of Principle on its Pathogenicity - Coutinho, Maria Francisca (2019)
Introduction: With its unprecedented throughput, scalability and speed, next-generation sequencing (NGS) is revolutionizing clinical research. Targeted sequencing in particular is now available in many labs. Still, whenever a novel variant is detected, its pathogenicity must be carefully assessed and every now and again, a case pops up to highlight how tricky and delicate this process can be. Here we present a case of a molecular diagnosis of a patient with a clinical suspicion of MPS type VI, where even though the causal mutation was easy to detect by both Sanger and NGS, only through indirect studies could we present proof of principle on its pathogenicity.